(untitled) (Health Renaissance, 2016)
Background: Tourism, a global industry, brings with it a number of public health problems, one of which is the spread of sexually transmitted infections transmitted between travellers and hosts. Previous studies have largely focused on sex workers and sex tourists. Objective: To assesses sexual behaviour, knowledge and condom use among male trekking guides in Nepal. Methods: A self-administered questionnaire survey (n=324) was conducted using snowball sampling amongst men working as mountain trekking guides in Nepal. Results: Most respondents (59%) had initiated sex before the age of 18. Most (84 %) reported sexual relations with a woman other than their partner, 46% reported foreign partners, 43% had Nepalese partners, and 28% had concurrent foreign and Nepalese partners. Most (70 %) reported ever having sex with a foreign woman and two-thirds had had sexual intercourse with foreign women in the previous 12 months. Participants’ age, education status, age of first sex, smoking and drinking habits and English proficiency were significant predictors of having sex with foreign women. About 60% reported condom use during their most recent occasion of extra-martial sex. A similar proportion had used a condom during last sexual intercourse with a foreign woman. The likelihood of condom use was associated with a guide’s age, educational level, ethnicity, age of first sex and work experience. Conclusions: Most trekking guides reported sexual relations with foreign women as well as irregular use of condoms. Although sexual health knowledge about among trekking guides is high, some misconceptions still result in unsafe sex. Hence there is an urgent need to revise the existing training for trekking guides and implement appropriate health promotion programmes. Health Renaissance 2014;12(3): 180-189